Current Portrayal of Character Education in Indonesian Children’s Books - Desi Yoanita; Kartika B. Primasanti (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2018)
Research studies in the western context indicated that the authors and illustrators have shown effort to depict character education effectively through children’s picture books. Conversely, in Indonesia, only few research studies regarding character education. A study was focused on how to use the books to promote character education. Another research was examining the types of moral values. None of the existed studies investigated approach to depict character education in Indonesia children’s picture books. Using semiotic method, this study indicated that among all significant components of portraying character education, the children’s books missed the two pivotal components, which are visual imagery and semiotic components.